Rancang Bangun Purwarupa Sistem Deteksi Tingkat Kematangan Buah Jeruk Berdasarkan Warna Kulitnya - Muhammad Taufiq Tamam; Arif Johar Taufiq; Wakhyu Dwiono (Jurnal Riset Rekayasa Elektro, 2020)
The process of selecting the level of maturity of an orange fruit can be done electronically, using a color sensor that will detect the color of the orange peel. Orange fruits will be grouped into two levels of maturity, namely unripe/raw and ripe. By using image processing techniques, the image of orange fruit to be selected is searched for components R (Red), G (Green), and B (Blue). If an average RGB value of less than 100 is categorized as mature and if more than 100 is categorized as immature/raw. The test results show that this system can work well as planned.